Management of Hypercholesterolemia Through Dietary ß-glucans–Insights From a Zebrafish Model - Gora, Adnan Hussain; Rehman, Saima; Kiron, Viswanath; Dias, Jorge; Fernandes, Jorge M. O.; Olsvik, Pål Asgeir; Siriyappagouder, Prabhugouda; Vatsos, Ioannis; Schmid-Staiger, Ulrike; Frick, Konstantin; Cardoso, Miguel (Frontiers in Nutrition, 2022)
Consumption of lipid-rich foods can increase the blood cholesterol content. β-glucans have hypocholesterolemic effect. However, subtle changes in their molecular branching can influence bioactivity. Therefore, a comparative investigation of the cholesterol-lowering potential of two β-glucans with different branching patterns and a cholesterol-lowering drug, namely simvastatin was undertaken employing the zebrafish (Danio rerio) model of diet-induced hypercholesterolemia. Fish were allocated to 5 dietary treatments; a control group, a high cholesterol group, two β-glucan groups, and a simvastatin group. We investigated plasma total cholesterol, LDL and HDL cholesterol levels, histological changes in the tissues, and explored intestinal transcriptomic changes induced by the experimental diets. Dietary cholesterol likely caused the suppression of endogenous cholesterol biosynthesis, induced dysfunction of endoplasmic reticulum and mitochondria, and altered the histomorphology of the intestine. The two β-glucans and simvastatin significantly abated the rise in plasma cholesterol levels and restored the expression of specific genes to alleviate the endoplasmic reticulum-related effects induced by the dietary cholesterol. Furthermore, the distinct patterns of transcriptomic changes in the intestine elicited by the oat and microalga β-glucans impacted processes such as fatty acid metabolism, protein catabolic processes, and nuclear division. Oat and microalgal β-glucans also altered the pattern of lipid deposition in the liver. Our study provides insights into the effectiveness of different β-glucans to alleviate dysfunctions in lipid metabolism caused by dietary cholesterol.